Nanotoxicity : Methods and Protocols - Reineke, Joshua; Ed (Humana Press, 2012)
The field of nanotechnology has developed very rapidly over the past decade lending great promise to medical applications in drug delivery, therapeutics, and biological imaging. Due to the great promise, rapid development, and broad application of nanomaterials, it is imperative that researchers from development through application seek a thorough understanding of nanotoxicity. Nanotoxicity: Methods and Protocols address the special considerations when applying toxicity studies to nanomaterials and detail newly developed methods for the study of nanotoxicity. These diverse methods span in vitro cell culture, model tissues, in situ exposure, in vivo models, analysis in plants, and mathematical modeling, proving to be relevant to pharmaceutical scientists, material scientists, bioengineers, toxicologists, environmentalists, immunologists, and cellular and molecular biologists, to name a few. As part of the highly successful Methods in Molecular Biology, chapters include introductions to their respective topics, lists of the necessary materials and reagents, step-by-step, readily reproducible laboratory protocols, and tips on troubleshooting and avoiding known pitfalls. Comprehensive and cutting-edge, Nanotoxicity: Methods and Protocols aims to diversify the capabilities of current researchers involved in nanotoxicology and to enable researchers in related fields to expand their knowledge of how nanomaterials interface with the biological environment.